Monitoring of zakat by the National Audit Department / Asmah Abdul Aziz … [et al.] - Abdul Aziz, Asmah; Ismail, Huzaimah; Abdul Rahman, Nafsiah; Mohd Jamil, Muslimah (2013)
There are many studies conducted as regards to the determinant of audit lags. This research determined the relationship between audit lags and the size of zakat institutions, types of institutions, types of audit reports, and amount of expenditure and preparation lags. In conjunction with that, the researcher also attempts to identify the comments from the auditors. This research could help the government to identify factors that could also help the government to evaluate the performance of the zakat institutions. These organizations also can identify factors that abstain the timeliness of audit reports. This is done by identifying the factors that prolong audit lags in zakat institutions. The audited financial statements and performance audit report from 2000 to 2009 were taken from the National Audit Department in Malaysia. There are many audit incidents in the financial statements and the performance reports. Size of zakat institutions, type of zakat institutions and preparation lags has significance relationship with audit lags. In addition, the issuance of comment short of audit qualification report was not due to the numbers of zakat audit incidents, since there is no report on the zakat alone. Audit recommendations regarding audit incidents in the performance report are also demonstrated.